Mulheres de Santa Mariana - PR entre as décadas de 1920 a 1940: uma leitura dos silêncios - Vitorini, Rosilene Alves da Silva (2021)
The present work seeks to understand how the historical narrative, constructed from official sources, invisibilizes and silences women and their contributions in society. To materialize this research, it was observed that in the official writing of the municipality of Santa Mariana - PR, some aspects were silenced, invisible, such as the absence of biographical information about Mariana, honored in the name of the municipality. It is noted in the official documents of the municipality of Santa Mariana a tendency to highlight and enhance the figure of the landowner, pioneering, based on a patriarchal conception. The investigative process is inscribed by documentary and bibliographic research, with a qualitative approach of a basic nature, reflecting on the historical conditions imposed on women and the construction of narratives anchored in the dominant economic knowledge. The study presents some theoretical categories such as historical narrative, processes of silencing and patriarchy, education as a strategy of resistance, starting from a local context to an expanded approach. Finally, the research allowed, in a brief way, to approach theoretical concepts, diverse social and historical contexts, and the social practice that in several aspects needs be strained in its structures, for the effective equity of conditions of access to rights and the overcoming of patriarchal thought, of domination and oppression.